Musik dan Gerak: Pendidikan Seni bagi Anak Usia Dini - Putu Sandra Devindriati Kusuma; Ni Made Dian Widiastuti; Ni Wayan Iriani (Journal of Music Science, Technology, and Industry, 2022)
Purpose: This study aims to look at the position of art education for early childhood. Art education for children this age is not only limited to singing or composing existing songs and changing the lyrics. Research Methods: This article is the result of a literature study which is strengthened by interviews with one of the educators who is also an early childhood education activist. The data presented in the form of descriptive text, so the nature of this research is descriptive analysis. Results and Discussion: The results of the study show that art is one aspect of development for early childhood is included in ministerial regulations and curriculum. The things that include in the art development program are the embodiment of an atmosphere for the development of exploration, expression, and appreciation of art in the context of play for early childhood. With the art aspect that has been regulated by the Indonesian government, from an early age children can practice their balance through art because art can inspire feelings and thoughts to be human. Implication: In this case, educators must be sensitive because art is to train sensitivity, such as observing children's responses when they hear music and then moving, observing children's body shapes when moving, and creating fun music and movement activities for early childhood to fill their development at in the golden age.